When the sky rained dust [large type] - Dearen, Patrick (Wheeler Publishing Large Print Softcover Western, 2023)
"Fourteen-year-old Josh and his friend Shan are facing hard times on their families' farms in Central Texas in 1934. It's the days of the Dust Bowl and Great Depression, and rain is as scarce as money. With the long dry spell have come wild animals with flashing teeth and deadly rabies. Dust storms known as black blizzards are raging, threatening lives and destroying cropland. Will a rainmaker bring rain? Will their families lose their homes? Will Josh's and Shan's friendship survive? From rabid animal attacks to a deadly flood to a barreling freight train, Josh is in for an adventure he will never forget"--